Kinetic Modeling of Convective and Microwave Drying of Potato Peels and Their Effects on Antioxidant Content and Capacity - Fatiha Brahmi; Inmaculada Mateos-Aparicio; Khokha Mouhoubi; Sara Guemouni; Tassadit Sahki; Farid Dahmoune; Ferroudja Belmehdi; Chafiaa Bessai; Khodir Madani; Lila Boulekbache-Makhlouf (MDPI AG, 2023)
This study deals with drying properties and focuses on the drying kinetics of potato peels (PP) by two processes, namely convection drying (CD) at various temperatures (40, 60, 80, 100, and 120 °C) and microwave drying (MD) at different powers (200, 400, 600, and 800 W). In addition, the effectiveness of the adopted processes was evaluated in terms of antioxidant contents and antioxidant capacity. A total of 22 mathematical models were undertaken to predict the drying kinetics, and the best model was selected based on the highest R2 values and the lowest χ2 and RMSE values. The Sledz model was the more appropriate for both methods with values of 0.9995 ≤ R2 ≤ 0.9999, χ2 = 0.0000, and 0.0054 ≤ RMSE ≤ 0.0030 for CD, and the results of MD were 0.9829 ≤ R2 ≤ 0.9997, 0.0000 ≤ χ2 ≤ 0.0010, and 0.0304 ≤ RMSE ≤ 0.0053. The best drying rates (DR) of PP were assigned to a temperature of 120 °C and a power of 600 W with values of 0.05 and 0.20 kg water/kg dw min, respectively. A potential explanation is that as PP's moisture content decreased during the drying process, there was a drop in absorption, which led to a reduction in the DR. The energy consumption of both processes was assessed, and it rose with increasing temperature or power. The microwave process reduced the drying time, consumed lower energy, and presented a higher drying efficiency at a moderate power level compared to the convection process. Furthermore, MD preserved antioxidants better compared to CD and improved the antioxidant capacity. Therefore, the proposed microwave process for drying PP is suggested for its expected use in various fields, including the food processing industries.